School Facilities and Infrastructure Management for Quality Improvement in Elementary Education - Arianto Arianto; Hera Yanti; Aminah Aminah (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The quality of education is fundamentally related to the accessibility and efficient administration of educational facilities and infrastructure. In several primary schools, deficiencies in the design, organization, implementation, and evaluation of facilities management frequently obstruct the attainment of optimal learning outcomes. This study seeks to examine the level to which the administration of educational facilities and infrastructure improves the quality of education in primary schools within Kuta Makmur District, North Aceh Regency. Data were gathered utilizing a qualitative descriptive methodology through in-depth interviews, observations, and document analysis including school principals, educators, and educational stakeholders. The findings indicate that methodical planning grounded in actual demands, well-defined organizational structures, consistent execution, and ongoing assessment of facilities management substantially enhance the development of a constructive learning environment. However, various issues endure, such as insufficient finance, feeble stakeholder participation, and deficient maintenance systems. The study indicates that reinforcing participative and sustainable management of facilities and infrastructure is crucial for improving educational quality. The findings offer actionable insights for educational leaders and policymakers in formulating more efficient facility management methods to enhance quality-focused elementary education.